Familial Hypophosphatemic Rickets - A Case Report and Review of Literature - Haque, Md Shahidul; Fatmi, LE; Alam Chowdhury, Md Shafiqul (Bangladesh Journal of Child Health, 2012)
DOI: http://dx.doi.org/10.3329/bjch.v34i2.10222 BJCH2010; 34(2): 73-75